Seasonal effect on the seminal characteristics of alpacas (Vicugna pacos) raised at sea level - Villanueva M., Juan C. (2018)
The objective of the present study was to evaluate the effect of the season (summer, winter) on the seminal variables of alpacas reared under conditions of the Peruvian coast. The study was conducted between January to September 2015 in Lima, Peru. Semen samples were collected from four 6-7 year-old male alpacas, fed alfalfa hay. Five collections per animal were made, using artificial vagina, in each season: summer (January-March) and winter (July-September) with intervals of 5 days between collections (20 collections per season). Macroscopic characteristics (volume, pH, viscosity, color) and microscopic characteristics (concentration, motility, vitality, percentage of abnormalities, tail and head abnormalities, proximal and distal cytoplasmic droplet, and endosmosis test) were evaluated. The results obtained in the winter showed significant differences (p<0.05) for concentration (135.9 ± 88.7 x 106/ml vs 242.4 ± 140.9 x 106/ml), motility (58.0 ± 22.1% vs 77.3 ± 11.6%), vitality (52.9 ± 18.4% vs 64.5 ± 15.9%), viscosity (5.9 ± 3.4 cm vs 3.7 ± 2.0 cm) and normal sperm frequency (82.6 ± 7.2% vs 88.1 ± 7.0%) for summer and winter, respectively. The results obtained indicate that the semen quality of alpacas, under the conditions of the study, differs between seasons.